2022
DOI: 10.1111/apt.17256
|View full text |Cite
|
Sign up to set email alerts
|

A prospective pilot study of a gluten‐free diet for primary sclerosing cholangitis and associated colitis

Abstract: Background: Primary sclerosing cholangitis (PSC) is a progressive bile duct disease associated with inflammatory bowel disease (PSC-IBD).Aim: To investigate whether patients with PSC-IBD benefit from a gluten-free and amylase trypsin inhibitor (ATI)-free diet (GFD). Methods:We performed a prospective clinical pilot study administering an eightweek GFD. The primary outcomes were colonic inflammation assessed by proctosigmoidoscopy, and liver stiffness (surrogate for fibrosis, inflammation and cholestasis) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…A recent study reported that a gluten-free and amylase trypsin inhibitor (ATI)-free diet might improve the biomarkers of intestinal inflammation and barrier function in IBD patients with associated changes in the gut microbiota, including a decrease in the pathogen Romboutsia ilealis. 47 In addition, Liu et al demonstrated that 2′-fucosyllactose (2′FL) and galactooligosaccharide (GOS) could alleviate DSS-induced colitis in mice accompanied with the inhibition of Romboutsia and the enrichment of Akkermansia , Bifidobacterium , Faecalibaculum , and unclassified_f_Lachnosipiaceae. 48 In our study, the level of Romboutsia was decreased in the colitic mice treated with Sal and FMT compared when compared with that of colitic mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that a gluten-free and amylase trypsin inhibitor (ATI)-free diet might improve the biomarkers of intestinal inflammation and barrier function in IBD patients with associated changes in the gut microbiota, including a decrease in the pathogen Romboutsia ilealis. 47 In addition, Liu et al demonstrated that 2′-fucosyllactose (2′FL) and galactooligosaccharide (GOS) could alleviate DSS-induced colitis in mice accompanied with the inhibition of Romboutsia and the enrichment of Akkermansia , Bifidobacterium , Faecalibaculum , and unclassified_f_Lachnosipiaceae. 48 In our study, the level of Romboutsia was decreased in the colitic mice treated with Sal and FMT compared when compared with that of colitic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic consumption increases R. ilealis levels [ 54 ] and decreases pro-inflammatory plasma cytokines. In primary sclerosing cholangitis with inflammatory bowel disease, gluten-free diets reduced R. ilealis [ 55 ]. Similarly, in mice studies [ 56 ] of colitis, selenium-enriched Lactobacillus acidophilus improved Romboutsia -promoted intestinal inflammation and significantly reduced their levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study of gluten-free diet (GFD), Liwinski and Hübener et al have made a first attempt to describe the molecular effects of a dietary intervention in PSC. 5 In the study, 15 individuals with PSC-IBD completed 8 weeks of GFD, aiming to test the impact on colonic inflammation (sigmoidoscopy) and liver stiffness. An association between coeliac disease and PSC is well known.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…The strong link between inflammation of both gut and liver points to the gut microbiome and interactions with dietary exposures as a potential player. In a pilot study of gluten‐free diet (GFD), Liwinski and Hübener et al have made a first attempt to describe the molecular effects of a dietary intervention in PSC 5 …”
mentioning
confidence: 99%